TINJAUAN YURIDIS TERHADAP PENGAWASAN PEREDARAN OBAT YANG TIDAK MEMENUHI SYARAT OLEH BADAN PENGAWASAN OBAT DAN MAKANAN REPUBLIK INDONESIA DARI SISI HUKUM PERLINDUNGAN KONSUMEN - , Inda Hudayani Rivai, SH, Prof. Dr. Nindyo Pramono, S.H., M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Advances in technology also has brought rapid and significant changes in the industrial world, one example is the phannaceutical industry. With the advances in technology it could make a pharmaceutical company in producing the medicine on a large scale. Drugs that will be or have been circulating within the community should meet the quality, safety and usefulness requirements. But in the reality, there are still many medicines who do not qualify as result of negligence or fraud by the pharmaceutical industry to produce a type of medicine that could affect the consumer health intentionally or not. The Supervisory Agency for Food and Drugs is a non-departmental bodies charged with monitoring the drug before and after circulating in the community. The Supervisory Agency for Food and Drugs to supervise with the premarket way which supervision conducted before the drug was circulated like an evaluation or assessment of safety, efficacy, quality and labeling of products in order to have marketing authorization. And post-market supervision includes monitoring of the drug products that have been circulating in the community, retesting of the drug product, information and education. If consumers consuming a type of drug that can cause negative impacts for themselves, then the consumer can file a lawsuit against a phannaceutical industry that produces the drug or the consumer can complain to the consumer complaint unit of the Supervisory Agency for Food and Drugs for observation and re-tests of the drug. This Legal research is based on the nature and purpose are classified as normative legal research, and has the aim to obtain the description, understanding, and explanation of the drugs that do not meet the requirements, supervision conductesiby the Supervisory Agency for Food and Drugs and remedies can be done by the cons~er if there is negative impact in taking a drug.